Effects of combined treatment of plasma activated liquid and ultrasound for degradation of chlorothalonil fungicide residues in tomato. (1st March 2022) - Ali, Murtaza; Sun, Da-Wen; Cheng, Jun-Hu; Johnson Esua, Okon
Graphical abstract: Highlights: PAL, ultrasound and their combinations were used for degrading fruit fungicide. Up to 89.28% of chlorothalonil from tomato were degraded with combined treatments. Five products were identified from the degradation pathway by plasma. The quality of tomato was not significantly affected by the treatments. Abstract: The effects of combined treatment (PAL-U) of plasma-activated liquid (PAL) including plasma-activated water (PAW) and plasma-activated buffer solution (PABS) and ultrasound (U) for the degradation of chlorothalonil fungicide on tomato fruit was investigated. Distilled water and buffer solution were activated by radiofrequency plasma jet for durations of 1, 3, 5, and 10 min to obtain PAL1 to PAL10 . Fruits were immersed in PAL for 15 min and also in distilled water with sonication for 15 min for individual treatments, and in PAL with sonication for 15 min for combined treatments. The maximum chlorothalonil fungicide residues were reduced by 89.28 and 80.23% for PAW10 -U and PABS10 -U, respectively. HPLC-MS characterization revealed chlorothalonil degradation pathway and formation of 2, 4, 5-trichloroisophthalonitrile, 2, 4-dichloroisophthalonitrile, 4-chloroisophthalonitrile, isophthalonitrile and phenylacetonitrile as degradation products. Treatments also showed no negative effects on tomato quality. Therefore, PAL and PAL-U treatments could serve as effective methods for degrading pesticides on tomatoes.